International Educational Migration in the Context of Martial Law - Cherusheva Н. B.; Parkhomenko, V. V. (Statistics of Ukraine, 2025)
Migration processes, being a distinct feature of any present-day country and having an objective nature, are an indicator of its socio-economic development. The central factor of migration across the global space is economic, pushing persons to migrate in search for comfortable living conditions, good salaries or labor market demand. The main category of migrants is a potentially employable and active population. The international educational migration in Ukraine, being a substantial component of Euro-integration processes, is largely responsible for high-quality training of future professionals for various economic sectors, helps enrich domestic labor capacities and highly skilled human resources for the development of national economy. The relevance of interdisciplinary approach to educational migration issues in the philosophical, socio-economic and legal context stems from the necessity for an integrated vision, understanding and analysis of social phenomena and processes. The educational migration as a trend within the global migration processes in the 21st century is an important dimension of the academic mobility aimed to diversify the sources of acquiring knowledge and new skills, on the one hand, and a manifestation of the economic globalization, on the other. Also, the pace of migration processes is determined by political and military conflicts. Ukraine is not an exception, as the outflow of various population strata has reached massive scales: women have been fleeing to get mental and physical protection, comfortable and favorable living conditions for their children; labor migrants have been leaving in search for jobs with sufficiently high salaries and consumption level, and this latter category has an impact on the socio-economic situation in the country. The article highlights peculiar features of migration processes in the context of martial law in Ukraine. A statistical analysis was used to determine changes and causes of the migration flows, and to reveal a tendency of the internal displacement of persons from the occupied territories. Emphasis was made on an analysis of the education migration of Ukrainian youth and determining main socio-economic factors of their going abroad. A factor analysis of the advantages encouraging Ukrainians to seek for education in Poland was made with consideration to the international migration specifics. Statistical data on the pace of education migration over the latest ten years are given; migration intentions of Ukrainian graduates from higher education institutions abroad are shown.